Estimation and evaluation of a segmented markets monetary model - John S. Landon-Lane; Filippo Occhino (Rutgers University, Department of Economics, 2005)
This paper develops a heterogeneous agents segmented markets model with endogenous production and a monetary authority that follows a Taylor-type interest rate rule. The model is estimated using Markov chain Monte Carlo techniques and is evaluated as a framework suitable for empirical monetary analysis. We find that the segmented markets friction significantly improves the statistical out-of-sample prediction performance of the model, and generates delayed and realistic impulse response functions to monetary policy shocks. In addition, we find that the estimates of the Taylor rule are stable across the pre-1979 and post-1982 periods in our sample, while the volatilities of the structural shocks faced in the pre-1979 period are substantially higher than in the post-1982 period.
Keywords: E52; C52; C11; 330; Segmented markets; Markov chain Monte Carlo; Taylor rule; Monetary policy shocks; Marktsegmentierung; Geldpolitik; Taylor-Regel; Schock; Theorie